Imaging, genetic and pathological features of vascular dementia - Yang, Xiaoni; Chen, Chao; Wang, Aishuai; Li, Changsheng; Cheng, Guangqing (European neurology, 2023)
Over the past decades, marked progress has been made in detecting vascular dementia (VD) both through maturation of diagnostic concepts and advances in brain imaging, especially MRI. We summarized the imaging, genetic and pathological features of VD in this review. It is a challenge for the diagnosis and treatment of VD, particularly in patients where there is no evident temporal relation between cerebrovascular events and cognitive dysfunction. In patients with cognitive dysfunction with post-stroke onset, the etiological classification is still complicated. In this review, we summarized the clinical, imaging and genetic as well as pathological features of VD. We hope to offer a framework to translate diagnostic criteria to daily practice, addresses treatment, and highlights some future perspectives.